1995
DOI: 10.1002/ps.2780440404
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of aldicarb sulfoxide and aldicarb sulfone in four water‐saturated sandy subsoils

Abstract: The transformation of aldicarb sulfoxide and aldicarb sulfone was studied in incubations with water‐saturated subsoils under simulated field conditions at 10°C. The subsoils were collected at four locations from beneath the water table at a depth of 2.5 to 3.5 m. In three of the subsoils, the half‐life of sulfoxide, incubated at concentrations of 0.14‐0.17 mg litre−1, ranged from 0.7 to 2.8 years. At higher concentrations (8‐13 mg litre−1), its half‐life ranged from 3.4 to 6.4 years. At the lower concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Pesticides volatise readily from coarsetextured soils; the texture of soil also affects the amount of pesticide that is lost due to run-off (Harrison, 1990). Smelt et al (1995) found the longest half-lives to occur in humic sandy soils, whereas the shortest were found in sandy loam soils.…”
Section: Soil Texturementioning
confidence: 95%
See 1 more Smart Citation
“…Pesticides volatise readily from coarsetextured soils; the texture of soil also affects the amount of pesticide that is lost due to run-off (Harrison, 1990). Smelt et al (1995) found the longest half-lives to occur in humic sandy soils, whereas the shortest were found in sandy loam soils.…”
Section: Soil Texturementioning
confidence: 95%
“…Degradation rates in subsurface layers might differ significantly from those in the surface layer because of changes in soil conditions such as organic matter content, microbial activity, moisture content and temperature (Fomsgaard & Albaiges, 1995;Smelt et al, 1995). Decomposition rates in subsoils are generally much slower than they are in surface soils, because microbial activity is much less deep in the soil (Bromilow et al, 1986).…”
Section: Soil Depthmentioning
confidence: 99%
“…An advanced method for collecting (anaerobic) soil material from depths of a few metres in the groundwater zone was described by Smelt et al 13 Plastic casing tubes fitted with a steel cutting ring were inserted into the soil and the soil material was removed from inside the tube by augering and bailing. When the boreholes were at the required depth, subsoil material from the permanently water‐saturated layer below was collected with a stainless steel sampling cylinder having a steel screw‐on cover incorporating a hole fitted with a connector from which a rigid plastic tube led to a switch.…”
Section: An Appraisal Of Experimental Methodsmentioning
confidence: 99%
“…The redox potential is an important characteristic of aquifers; it can be measured both in the field and in the laboratory by using a platinum electrode and a silver/silver chloride reference electrode, connected to a voltmeter. Long electrodes can be used in the field measurements: a piece of platinum wire extending from a rubber stopper at the bottom end of a long poly(methacrylate) tube can be connected via an internal copper wire to the voltmeter 13. The reference electrode is connected to the groundwater via a salt bridge consisting of a potassium chloride solution in a polythene tube provided with a tensiometer cup at the end.…”
Section: An Appraisal Of Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation